2012
DOI: 10.1111/j.1439-0396.2012.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pancreatic exocrine secretion in goats: differential effects of short‐ and long‐term duodenal phenylalanine treatment

Abstract: Four yearling goats (31.2 ± 2.5 kg), surgically fitted with common bile duct reentrant and duodenal catheter, were used in two 4 × 4 Latin square design experiments to investigate the effects of duodenal infusion of phenylalanine for different times on pancreatic exocrine secretion (PES). In experiment 1 (the long-term experiment), goats were duodenally infused with 0, 2, 4 or 8 g/day phenylalanine for 14 day. Pancreatic juice and jugular blood samples were collected over 1-h intervals for 6 h daily from day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 30 publications
4
25
2
Order By: Relevance
“…Yet, hydrolysis of small-chain α-glycosides apparently increased 32% by NEAA compared with EAA (measured as a decrease in flow of ethanol-soluble starch to the ileum), which suggests that the hydrolytic capacity of bovine small intestine for small chain α-glycosides was appreciably increased in response to nonessential AA. Yu et al (2013) reported that duodenal infusion of Phe decreased pancreatic α-amylase secretions in goats. In the current experiment, small intestinal starch digestion was not different from the control when PTM was infused, and flows of ethanol-soluble starch were not different from the control when PTM alone was infused.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, hydrolysis of small-chain α-glycosides apparently increased 32% by NEAA compared with EAA (measured as a decrease in flow of ethanol-soluble starch to the ileum), which suggests that the hydrolytic capacity of bovine small intestine for small chain α-glycosides was appreciably increased in response to nonessential AA. Yu et al (2013) reported that duodenal infusion of Phe decreased pancreatic α-amylase secretions in goats. In the current experiment, small intestinal starch digestion was not different from the control when PTM was infused, and flows of ethanol-soluble starch were not different from the control when PTM alone was infused.…”
Section: Discussionmentioning
confidence: 99%
“…However, longterm leucine supplementation does not increase muscle mass in healthy elderly men (Verhoeven et al, 2009;Leenders et al, 2011). Our previous research also shows that duodenal infusion of phenylalanine for a short (10 h) or long period (14 days) has different effects on pancreatic exocrine secretion in goats (Yu et al, 2012). These results indicate that the acute regulating roles of leucine towards pancreatic exocrine secretion may differ from those of prolonged treatment.…”
Section: Introductionmentioning
confidence: 87%
“…In our recent report, duodenal infusion of phenylalanine for 14 days has been verified to be an effective regulating factor for pancreatic a-amylase secretion of goats (Yu et al, 2012). In rats, leucine not only decreases a-amylase mRNA expression (Hashimoto and Hara, 2004), but also stimulates pancreatic protein synthesis dependent on the mammalian target of rapamycin (mTOR) signalling pathway (Sans et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…The milk fed to all the groups was made isonitrogenous by adding alanine (1.366, 0.391, 0.975, and 0 g/L of milk for control, leucine, phenylalanine, and mixed treatments, respectively). The doses of leucine and phenylalanine for the experimental groups were based on the results of Yu et al (2013) and Liu et al (2015). The milk was sampled weekly and stored at −20°C, and the samples were pooled.…”
Section: Animals Experimental Design and Dietsmentioning
confidence: 99%
“…Cholecystokinin can promote the synthesis of pancreatic amylase, trypsin, and trypsinogen, stimulate the release of these pancreatic enzymes, and enhance their activities. Duodenal infusions of phenylalanine (Yu et al, 2013) and leucine (Liu et al, 2015) play a role in regulating the secretion of pancreatic α-amylase.…”
Section: Introductionmentioning
confidence: 99%